Alternative urban exchange rethinking the Plaza Complex of Santa Cruz, Laguna - Dela Rosa, Patrick Lawrence E.; Sorupia, Eden (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Plazas can be dated way back during the Spanish period through the Laws of the Indies enacted during the reign of King Philip II. It enforced a set of guidelines placing the plaza at the city's center. Plazas serve as a place for congregation, civic identity and also as a form of refuge and relief from built spaces. As developers move through capitalist-driven agendas, less ecologically sustainable means, and resulting to lower quality of life, we see the loss of societal and cultural value for our open spaces. Among its adverse effects is our plazas increasing disjointedness from our communities, caused by roads that limit pedestrian pull. Santa Cruz exhibits the very. Same. Symptoms.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Plazas; Plazas -- Laguna -- Philippines